2001
DOI: 10.1016/s1463-5003(01)00005-1
|View full text |Cite
|
Sign up to set email alerts
|

Some thoughts on the freezing and melting of sea ice and their effects on the ocean

Abstract: Abstract. The high-latitude freezing and melting cycle can variously result in haline convection, freshwater capping, or freshwater injection into the interior ocean. An example of the latter process is a secondary salinity minimum near 800 m depth within the Arctic Ocean that results from the transformation on the Barents Sea shelf of Atlantic water from the Norwegian Sea and its subsequent intrusion into the Arctic Ocean. About onethird of the freshening on the shelf of that initially saline water appears to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…A simulation also indicated very large interannual variability (from 143 to 1236 km 3 yr À1 ), and this caused substantial variability in annual ice melt and freshwater content that affected the stratification, vertical mixing rates, and heat loss from the Atlantic Water . This finding is in line with Aagaard and Woodgate [2001] who also found that ice import, melting, and freshwater injection into the interior ocean are important processes in the northern Barents Sea.…”
Section: Maintenance Of the Arctic Layersupporting
confidence: 91%
See 1 more Smart Citation
“…A simulation also indicated very large interannual variability (from 143 to 1236 km 3 yr À1 ), and this caused substantial variability in annual ice melt and freshwater content that affected the stratification, vertical mixing rates, and heat loss from the Atlantic Water . This finding is in line with Aagaard and Woodgate [2001] who also found that ice import, melting, and freshwater injection into the interior ocean are important processes in the northern Barents Sea.…”
Section: Maintenance Of the Arctic Layersupporting
confidence: 91%
“…With the rapid climatic changes observed in the Arctic as a whole and the more regional warming in the Barents Sea, significant changes are expected in the ocean climate in the northern Barents Sea. Processes in the Barents Sea may, due to the water mass exchange across the northern and eastern boundaries of the Barents Sea, influence the properties of the halocline, the Atlantic Water (AW) and the intermediate water in the Arctic Ocean (e.g., Schauer et al, 1997;Aagard and Woodgate, 2001). Changing physical conditions in the Barents Sea will also have an impact on the Barents Sea ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The BS plays an important role in the Northern Hemisphere climate (Smedsrud et al, 2013) by ventilating the Arctic Ocean with the dense Barents Sea Water (Aagaard and Woodgate, 2001;Schauer et al, 2002) and by being a place of high primary productivity . The BS water masses delimited by several fronts are of particular interest.…”
Section: Objectivesmentioning
confidence: 99%
“…The modification of the AW taking place in the Barents Sea is therefore of great importance for the ventilation of the Arctic Ocean (Maslowski et al 2004;Schauer et al 2002;Aagaard and Woodgate 2001). AW enters the Barents Sea across the western open boundary, often called the Barents Sea Opening (BSO) (Loeng 1991).…”
Section: Introductionmentioning
confidence: 99%
“…There is significant modification of the waters in the Barents Sea (Furevik 2001;Gammelsrød et al 2008;Rudels et al 2004;Schauer et al 2002), and ice dynamics plays an important role (Budgell 2005;Kwok et al 2005;Aagaard and Woodgate 2001). AW looses heat due to atmospheric cooling, radiation, and ice melt.…”
Section: Introductionmentioning
confidence: 99%